Applicability of the Test of Variables of Attention – T.O.V.A in Brazilian adults - Memória,Cláudia M. (2018)
ABSTRACT The functioning of attention is complex, a primordial function in several cognitive processes and of great interest to neuropsychology. The Test of Variables of Attention (T.O.V.A) is a continuous computerized performance test that evaluates some attention components such as response time to a stimulus and errors due to inattention and impulsivity. Objective: 1) To evaluate the applicability of T.O.V.A in Brazilian adults; 2) To analyze the differences in performance between genders, age ranges, and levels of education; 3) To examine the association between T.O.V.A variables and other attention and cognitive screening tests. Methods: The T.O.V.A was applied to 63 healthy adults (24 to 78 years of age) who also underwent the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Digit Span and Digit Symbol (Wechsler Intelligence Scale for Adults – WAIS-III) and the Trail Making Test. Results: the T.O.V.A was little influenced by age or education, but was influenced by gender. The correlations between some T.O.V.A variables and the Digit Symbol and Trail Making test were weak (r-values between 0.2 and 0.4), but significant (p<0.05). There was no correlation with the Digit Span test. Conclusion: The T.O.V.A showed good applicability and proved adequate for evaluating attentional processes in adults.